1977
DOI: 10.1161/01.res.40.5.489
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the antibiotic ionophore X-537A on contractility and ionic exchange in rabbit ventricular myocardium.

Abstract: SUMMARY The effects of the ionophore X-537A on mechanical function and on ionic exchange were studied in the isolated, arterially perfused rabbit interventricular septum. X-537A produced an initial positive inotropic response which was, however, transient in this preparation and appeared to be dependent on an effect of the ionophore on catecholamines. The positive inotropy gave way to a progressive decline in force development which was unrelated to the action of catecholamines and was not accompanied by the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1980
1980
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 38 publications
(36 reference statements)
0
1
0
Order By: Relevance
“…There is also unambiguous evidence by Pascual et al [12] showing that the catecholamines dopamine and norepinephrine, as well as lasalocid, also participate in the contraction cardiac cycle and in the contractile inotropic properties of ventricular muscle through a Ca 2+ independent process [27]. Preceded by findings showing that the Ca 2+ ionophore also liberates dopamine from synaptosomal membranes from rat heart [13] and from isolated heart chromaffin vesicles [11], where Holz [10] showed that lasalocid also transports the neurotransmitters norepinephrine and dopamine, through artificial bimolecular lipid membranes.…”
Section: Discussionmentioning
confidence: 99%
“…There is also unambiguous evidence by Pascual et al [12] showing that the catecholamines dopamine and norepinephrine, as well as lasalocid, also participate in the contraction cardiac cycle and in the contractile inotropic properties of ventricular muscle through a Ca 2+ independent process [27]. Preceded by findings showing that the Ca 2+ ionophore also liberates dopamine from synaptosomal membranes from rat heart [13] and from isolated heart chromaffin vesicles [11], where Holz [10] showed that lasalocid also transports the neurotransmitters norepinephrine and dopamine, through artificial bimolecular lipid membranes.…”
Section: Discussionmentioning
confidence: 99%